Slovo . Slovo . Word . Слово - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Presentations by poets and prose writers. Featured in the program: Akhmadulina, Bella Akhatovna (Poet); Bitov, Andrei Georgievich (Writer); Zhvanetskii, Mikhail Mikhailovich (Writer) Выступления поэтов и писателей. В программе участвуют: Ахмадулина, Белла Ахатовна (Поэтесса); Битов, Андрей Георгиевич (Писатель); Жванецкий, Михаил Михайлович (Писатель)